O-022 Final reperfusion modifies the impact of IV-tPA on the outcome after mechanical thrombectomy for anterior circulation large vessel occlusion strokes. (23rd July 2022) - Mohammaden, M; Adelhamid, H; Haussen, D; Al-Bayati, A; Nogueira, R
Abstract : Background: Adjunct intra-arterial tPA following successful reperfusion with mechanical thrombectomy (MT) has been reported to improve outcomes. We sought to evaluate the impact of pre-procedural IV-tPA on functional outcomes after achieving full reperfusion with MT. Methods: A prospectively collected MT database from October 2010 to June 2021 was reviewed. Patients were included if they had anterior circulation large vessel occlusion strokes secondary to ICA or MCA-M1/M2 occlusion, pre-morbid modified Rankin Scale ≤2, last known well (LKW) to puncture time≤6 hours, and baseline extended Thrombolysis In Cerebral Infarction (eTICI) score of 0. The cohort was divided into two groups: bridging (pre-procedural IV-tPA plus MT) and non-bridging (MT alone) groups. Matching analysis was performed to balance the two groups. Subgroup analysis was performed to identify the effect size of pre-procedural IV-tPA on functional independence (90-day mRS0–2) as a function of final reperfusion grade: full reperfusion (eTICI3) vs. non-full reperfusion (eTICI<3). The secondary outcome included a 90-day mRS shift analysis. Safety measures included symptomatic intracranial hemorrhage (sICH) and 90-day mortality. Results: Among 823 patients eligible for the analysis, 564 were matched in a 1:1 ratio. The two groups were balanced in baseline and clinical characteristics. Final reperfusion grade significantly modified the effect of pre-procedural IV-tPA on functional independence (P=0.008), where bridging therapy showed higher rates of functional independence (63.2% vs. 51.6%, adjusted OR 2.09, 95%CI[1.03–4.20), P=0.039) compared to non-bridging therapy in patients with full reperfusion. However, in non-fully reperfused patients, the rates of functional independence were comparable (40.3% vs. 43.7%, adjusted OR 0.62, 95%CI[0.31 to 1.25], P=0.18) among both therapies. Likewise, bridging therapy was associated with 90-day mRS shift to a lower degree of disability (adjusted common OR 1.59, 95%CI [1.03–2.48], P=0.039) in fully reperfused but not in non-fully reperfused (adjusted common OR 0.98, 95%CI [0.65–1.46], P=0.91). The effect size of pre-procedural IV-tPA on functional independence was comparable across different subgroups ( figure 1 ). The rates of sICH and 90-day mortality were similar among bridging vs. non-bridging in fully and non-fully reperfused patients. Conclusion: The impact of pre-procedural IV-tPA on functional outcome was evident in patients who achieved full reperfusion compared to non-fully reperfused patients. Our findings could be related to the effect of the remaining tPA in circulation on improving intracranial microcirculation and hence preventing the no-reflow phenomenon. Further studies are warranted to validate our results. Disclosures: M. Mohammaden: None. H. Adelhamid: None. D. Haussen: 2; C; Stryker and Vesalio. 4; C; Viz.AI. A. Al-Bayati: 2; C; Stryker Neurovascular. R. Nogueira: 2; C; Stryker Neurovascular, Cerenovus, Medtronic, Phenox, Anaconda, Genentech, Biogen, Prolong Pharmaceuticals, Imperative Care. 4; C; Brainomix, Viz-AI, Corindus Vascular Robotics, Vesalio, Ceretrieve, Astrocyte and Cerebrotech.